Village-Owned Enterprises (Bumdes) as an Instrument of Community Welfare: an Analysis in Maqashid Syariah Perspective - Rizal Ancu; Rahman Ambo Masse; Irwan Misbach (LP2M IAIN Palopo, 2025)
This study aims to analyze Village-Owned Enterprises (BUMDes) as an instrument of community welfare from the perspective of Maqashid Syariah, with a case study on BUMDes Putra Perintis in Bonto Baji Village, Kajang District, Bulukumba Regency, South Sulawesi Province. The problem formulation in this study includes: (1) The role of BUMDes in improving community welfare in various aspects of life; (2) Application of Maqashid Syariah principles in BUMDes management and programs; and (3) Challenges in implementing Maqashid Syariah principles and supporting factors for the successful implementation of Maqashid Syariah principles in BUMDes. This study uses a qualitative approach with a case study method. Data were obtained through observation, interviews, and documentation, with key informants consisting of the BUMDes Director, BUMDes business actors, and the local community. Data analysis was carried out based on the Maqashid Syariah approach which includes the material and spiritual dimensions of the community. The results of the study indicate that BUMDes Putra Perintis has implemented Maqashid Syariah principles in the management and implementation of its programs, which has a positive impact on improving community welfare both materially and spiritually. However, public understanding of the Maqashid Syariah concept remains limited, necessitating increased outreach. The main challenges include limited human resources and limited access to information. Despite this, the successful implementation of Maqashid Syariah in Bonto Baji Village is supported by the active role of the village government and community participation.